Access to and Utilization of Wild Species for Food and Nutrition Security in Teso and Acholi Sub-regions of Uganda - Ekesa, Beatrice; Fongar, Andrea; Nasser, Mulumba (Frontiers in Sustainable Food Systems, 2022)
Wild foods play an important part within the global food basket, contributing to food and nutrition security. However, wild species are often forgotten within nutrition-related policies and their level of availability remains unknown. This paper, therefore, focuses on the changes in availability, access and utilization of wild animal and plant species in Teso and Acholi sub-regions of Uganda. A four-cell agrobiodiversity mapping protocol was applied through focus group discussions to establish the different wild animal and plant species that have played and still play a role within the livelihoods of the local communities in the two sub-regions. Findings showed that more than 120 edible wild species were reported to be available 20years ago in both Acholi and Teso sub-regions. Nevertheless, considering the period when this data was collected (2017) wild foods are still a contributor to food and nutrition security although the number of species reported was slightly lower 115 (Acholi) and 110 (Teso). Reasons for the decline included increased cultivation and the destruction of natural habitats due to settlements, changes in land ownership where individual owners further fragment their land and do not allow villagers to freely participate in hunting and gathering. Lastly, rebel unrest increased feelings of insecurity thus a decline in hunting and gathering ventures. The noted presence and contribution of wild foods, in Teso and Acholi, calls for collective effort in increasing access to knowledge on the value of these wild foods for not only food and nutrition but also their potential contribution to the social and cultural lives of the people.